Student personality development through excellent student personality program (SUMUR) in Malaysia - Musa, Nor Anisa (Penerbit Kolej Universiti Islam Antarabangsa Selangor, 2022)
Programs in schools, especially learning outside the classroom, play a role in shaping the personality of students by emphasizing the values of good personality. Every student needs to have a high level of personality by practicing a religious way of life, appear polite, courteous, have a sense of identity and various other things related to psychology that can be formed in oneself consistently. The formation of a superior personality in school is one of the goals that need to be achieved after learning or during activities regardless of demographic limitations such as religion, race, gender, location or school category. The Ministry of Education Malaysia (MOE) is a government agency that is responsible and plays a role as the main channel in emphasizing the formation of students' superior personality. The implementation of the Student Excellence Program (SUMUR) by the MOE is a significant program with the need for students with the concept of modularactivities and assessment throughout schooling at the secondary level. The assessments contained in the Program help improve the student achievement index. Thus, this article discusses past research highlights of matters that have a relationship with student personality such as emotional intelligence, engagement and resilience.